THE DETERMINANTS OF CONSUMER TRUST IN THE BANKING INDUSTRY IN ZIMBABWE - SANDADA, Maxwell; MAGOBEYA, Again (Studia Universitatis Babeș-Bolyai Oeconomica, 2016)
The purpose of this study is to examine the determinants of customer trust in the Zimbabwean banks. The study determines the effect of bank competence, bank integrity, benevolence, structural assurance and service recovery on customer trust. The data were collected by self-administered questionnaires and analyzed by correlation and multiple regression analysis. The results indicated that benevolence, structural assurance, and service recovery exhibit a statistically significant influence on customer loyalty in the context of Zimbabwean banks. By contrast, bank competence and integrity have an insignificant effect on customers’ trust. The study concludes that in the context of Zimbabwean banks, in order to influence customer loyalty, banks need to invest in service recovery programs, display benevolent character and assure customers of quality service. JEL Classification: G2, M2